Agribusiness in the Vision of Rural Youths: A Study in Odisha (Indian Journal of Extension Education, 2011)
Agri-business is gaining more attention in the domain of entrepreneurship development. It has been realized that small enterprises, like agri-business run by rural youths can contribute significantly to economic growth and poverty elimination program. But sometimes it happens that the stakeholders do not become serious in this profession. Keeping this in view, a study was undertaken in the coastal belt of Odisha to examine the status of agri-business in relation to rural youths. A sample of 80 youths fulfilling the criteria was randomly selected to form the sample size. A well tested interview schedule was used for data collection along with intimate interaction. The data so collected were statistically analyzed to reveal relevant information. The result indicate that rural youths lack many of the entrepreneurial traits like ability to identify opportunities, commitment, optimism, creativeness, hard work, achievement orientation, creating a gap in between expected and existing situation. These traits should be induced in them before the youths are motivated for agri-business. The study also examined the knowledge of respondents about scanning of opportunities with respect to agri-business. However, the sample lack in the areas of net-working, ideas of resource availability, market analysis, vision and overall ideas about project formulation. In case of factors like problem identification, need analysis, creativity, locating resources and change perception, the respondents possess considerable knowledge. Through a focus group discussion, the rural youths mentioned seed production as most profitable agro-enterprise which was ranked fiest followed by vegetable farming (II), growing of scented rice (III), oil seed production (IV) and goat rearing (V) and comparatively less preference for agro-processing unit, agro-science center, fingerlings production, raising planting materials and floriculture. For promotion of agri-business, the important environmental factors identified were market demand (2.62), labor (2.35) and credit (2.27). The other factors mentioned were found to be preference of consumer, technical support, training, storage facility and market survey.